Institutional and Technological Foundations of Economic Integration in Post Soviet Countries via Decentralized Financial Flows - Turyan, Karen Vladimirovich (Journal of Posthumanism, 2025)
This study examines how decentralized financial flows - including blockchain technologies, cryptocurrencies, fintech platforms, and central bank digital currencies - have influenced economic integration in post-Soviet countries from 2000 to 2025. Framed within the broader processes of digital transformation and institutional change, the research addresses the demand for alternative financial infrastructure in transitional economies. Employing a mixed-methods approach, it combines cross-country analysis with case studies to assess digital infrastructure, regulatory adaptation, financial inclusion, and DeFi adoption. Findings show that while digital connectivity has increased, decentralized finance usage varies based on institutional and socio-economic conditions. Countries facing financial shocks often adopted DeFi from the bottom up, while others pursued top-down regulatory strategies. The study concludes that decentralized finance is already enhancing integration by improving access to payments, savings, and public services.